Volume 1: Turbomachinery 1995
DOI: 10.1115/95-gt-082
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Study of a Radial Compressor Inlet

Abstract: Flow field measurements and flow visualization for a quarter scale model of a radial compressor inlet are presented for varying flow rates and inlet profiles. Non-uniform inlet profiles are created using a 90° bend directly upstream of the inlet. Experimental results are compared with the CFD analysis from a commercial 3-D Navier Stokes code. The experimental and computational results show good agreement, even in regions of reverse flow. The results from this study show CFD analysis can be used with confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…It serves the purpose of guiding the incoming radial flow into the axial direction. As has been shown and discussed in previous works, such as [14][15][16][17][18], a radial inlet can result in flow distortion in both the radial and circumferential directions.…”
Section: Introductionmentioning
confidence: 85%
“…It serves the purpose of guiding the incoming radial flow into the axial direction. As has been shown and discussed in previous works, such as [14][15][16][17][18], a radial inlet can result in flow distortion in both the radial and circumferential directions.…”
Section: Introductionmentioning
confidence: 85%
“…The flow angles, static pressures and total pressures at 50 sampling points were measured, and the distribution of total pressure loss coefficients was given. Koch et al 14 conducted an experimental study on an IC with different inlet pipes, and found that guide vanes arranged in the IC increased flow losses but benefited to overcoming flow distortions at the outlet section. Giachi and Taddei, 15 Michelassi and Giachi, 16 Michelassi et al, 17 and Pazzi and Michelassi 18 used a combination of experimental and numerical methods to study an inlet chamber of a centrifugal compressor with the model structure scaled at 1:2.5.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, researchers have either analyzed the components separately [3,4], or patched the components together, achieving a one-way coupling [5].…”
Section: Introductionmentioning
confidence: 99%